Remediation of Ultisol Soil by Biosilica for Cultivation of Soybean (Glycine max) - John Bimasri; Nely Murniati (JURNAL BUDIDAYA PERTANIAN, 2022)
Ultisol soil is erosion-sensitive and undergoes high nutrient leaching causing low silica content. This study aimed to improve the availability of silica in Ultisol soil by the addition of biosilica derived from rice husk ash for the cultivation of the soybean Derap 1 variety. This study WAS CARRIED OUT in Rahma Village, South Lubuklinggau I subdistrict, Lubuklinggau City, South Sumatera Province (-3018'10'',102054'41'') on 110.5 meters above sea level. This study was conducted from August to November 2021. This was an experimental study that used Randomized Block Design (RBC) with 6 treatment levels and 4 blocks as replicates. The treatments tried were the provision of biosilica at 0 kg/ha (B0 as control), 75 kg/ha (B1), 150 kg/ha (B2), 225 kg/ha (B3), 300 kg/ha (B4) and 375 kg/ha (B5). This study used 24 plots with a size of 2 m × 2 m for every plot. The seeds were planted at a distance of 40 cm × 40 cm, the population of each plot is 20 plants, with 5 diagonally determined samples. Soybean yield was harvested at 84 days of age after planting. Plants were fertilized at doses of 23 kg/ha NO3, 55 kg/ha K2O, and 18 kg/ha P2O5 that were given twice. Variables observed included plant height, number of primary branches, number of pods of each plant, the weight of 100 seeds, and yield per ha. The data were analyzed by Analysis of Variance using SAS software version 9.4 and tested with a Diversity Coefficient at the test level of 1%. It can be concluded from this study that rice husk ash is 375 kg/ha.was able to increase the pH of Ultisol soil. Soil Ultisol that was given biosilica from rice husk ash was able to increase the growth and yield of soybean. Derap 1 variety soybean yield from plants grown on the soil that was given biosilica from rice husk ash increased between 12 and 16%.